A Novel Approach for Pivacy preserving using Animal Migration Optimization and RSA algorithm - Bairagi, Nivedita; Punit K, Johari (International Journal of Computer Sciences and Engineering, 2025)
In recent years, the quantity of data between organizations, companies and governments has been produced and transmitted with extremely increased in number. Privateness preserving is without doubt one of the primary challenges in a computer world, when you consider that of the large amount of sensitive information on the internet. Additionally, with the quick increase of data mining technologies hidden relationships between items in databases can now be exposed with ease, for the reason of decision making or to determine user’s preferences. In the existing work, k-anonymity method used for the safety of sensitive data from the leakage or distribution to unauthorized users. However it is not sufficient for the protection of attribute disclosure. This method is also difficult to reverse the data to get the content. To overcome this problem, we performed the Animal Migration Optimization on the basis of age and then encryption is performed using RSA algorithm for achieving the security of the data and preserve from heavy data loss.